Comparing Vaginal Misoprostol and Vaginal Dinoprostone on the Rate of Vaginal Delivery within 24 Hours - Syaharani, Nabilla; Safitri, Yolanda; Saputri, Vivi Saharani; Salsabilla, Azira Isnaini; Yahya, Nur Khalisha; Yudistira, Dimas (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Labor induction with misoprostol and vaginal dinoprostone remains controversial regarding its effectiveness in achieving vaginal delivery within 24 hours. Objective: To compare the efficacy and safety of misoprostol versus dinoprostone in term pregnancies. Methods: An Evidence-Based Clinical Review (EBCR) synthesized RCTs and meta-analyses using the PICO framework (Population: term pregnant women; Intervention: dinoprostone; Comparison: misoprostol; Outcome: vaginal delivery <24 hours). PubMed, Cochrane, and EBSCO were searched October 2025. The CEBM tool identified 3 studies (1 RCT, 2 meta-analyses). PRISMA 2020 guided the narrative synthesis. Population/Sample: Term singleton pregnancies; 3 included studies (Gaudineau et al., 2021; Lakho et al., 2024; Ramadan et al., 2024). Analysis: A critical appraisal assessed validity, effect size (RR, NNT), and heterogeneity (I²). Results: Misoprostol resulted in higher vaginal delivery rates (Gaudineau: RR 1.30, NNT 7; Ramadan: RR 1.15, 95% CI 1.08-1.22; Lakho: RR 1.08). Conclusion: Vaginal misoprostol was superior or equivalent, providing cost-effective advantages for limited facilities.